Implementasi Kebijakan Peraturan Daerah Kabupaten Deli Serdang Nomor 07 Tahun 2015 Tentang Ketentraman & Ketertiban Umum Terhadap Pedagang Kaki Lima Dalam Perspektif Fiqh Siyasah - Lidya; Shaila Aulia prilini; halid andriansyah; Naufal akbar; ahmad mufti farid (Tabayyun : Journal Of Islamic Studies, 2024)
This article examines the control of street vendors as stated in the Deli Serdang Regency Regional Regulation No. 07 of 2015 concerning peace and public order. aims to determine the supervision, guidance and counseling of street vendors who trade on the sidewalk as stated in the Regional Regulations. This research uses a qualitative method, namely by using a descriptive analysis approach. The results of the research show that the implementation of Deli Serdang Regency Regional Regulation Number 07 of 2015 concerning Public Peace & Order on Jalan Medan - Batang. The Gambir Tembung Tax Quiz has been implemented well by the Deli Serdang Regency Satpol PP involving Satpol PP and the Head of Bandar Klippa Village in the form of visits to traders at the location to provide guidance, supervision, counseling and sanctions and does not conflict with the principles of the siyasa fiqh perspective.